Karakteristik Demam Typoid Dengan Uji Tubex Positif Pada Usia Anak Di Rumah Sakit Umum Daerah Lubuk Pakam Tahun 2017 - Annisa Rahmadayani; Said Munazar Rahmat (JURNAL PANDU HUSADA, 2020)
Abstract: Typhoid fever is one of the health problems in Indonesia as adeveloping country in the world. Typhoid fever can affect anyone, includingchildren. Typhoid fever at the age of the child varies in the clinical picture so it isdifficult to make a diagnosis and treat the disease. This study used a descriptiveresearch method and used secondary data taken from the medical records of DeliSerdang Lubuk Pakam Hospital in children with typhoid fever in 2017. Thenumber of samples in the study was obtained by the total sampling method. Fromthe results of the study, there were male patients (55.6%), and 92 women (44.4%).Patients aged 29 days to 2 years was 31 (15%), ages above 2 years to 6 years was70 (33.8%) aged over 6 years to 15 years was 106 (51.2%). Clinicalmanifestations found in the form of 207 cases by fever (100%), vomiting by 156persons (75.4%), nausea by 125 persons (60.4%), diarrhea by 80 persons(38.6%), abdominal pain by 82 persons (39.6%), cough by 73 persons ( 35.3%),headache by 14 persons (6.8%), constipation by 28 persons (13.5%), and dirtytongue by 43 persons (20.8%). Uncomplicated patients by 202 person (97.6%),anemia complications by 2 people (1%), bronchopneumonia by 1 person (0.5%),bronchitis by 1 person (0.5%), seizures by 1 person (0.5%). Most people withtyphoid fever in the Deli Serdang Lubuk Pakam Regional General Hospital aremale, aged over 6 years to 15 years, manifest fever, and the most commoncomplication is anemia.Keywords: typhoid fever, children, characteristics, tubex test